Pandangan Fiqih Islam Tentang Etika Menutup Aurat di Media Sosial - Uswatun Hasanah; Dila Purwa Lestari; Aulia Mayada (Indo Publishing, 2026)
This study examines Islamic jurisprudence (fiqh) perspectives on the ethics of covering the genitals (awrah) on social media as a form of implementing sharia values in the digital era. Public social media often becomes a space for violations of the boundaries of genitals (awrah), especially among Muslim women. Using descriptive qualitative methods, this study analyzes Quranic verses, hadiths, and the views of scholars from various fiqh approaches. The results of the discussion indicate that the law of covering genitals remains valid in both the real world and the virtual world, as both are public spaces accessible to many people. The ethics of covering genitals on social media require caution in dress, uploading content, and keeping views away from things that are forbidden. Thus, maintaining genitals (awrah) on social media is not only an individual obligation, but also part of maintaining the self-respect and dignity of Muslims.